2021
DOI: 10.3390/ijms23010084
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Assessment of Genetic and Epigenetic Alterations Identifies Frequent Variations Impacting Six Prototypic SCF Complex Members

Abstract: The SKP1, CUL1, F-box protein (SCF) complex represents a family of 69 E3 ubiquitin ligases that poly-ubiquitinate protein substrates marking them for proteolytic degradation via the 26S proteasome. Established SCF complex targets include transcription factors, oncoproteins and tumor suppressors that modulate cell cycle activity and mitotic fidelity. Accordingly, genetic and epigenetic alterations involving SCF complex member genes are expected to adversely impact target regulation and contribute to disease eti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 108 publications
0
1
0
Order By: Relevance
“…While Schedel et al identified a germline variant in RAD21 that can predispose to childhood lymphoblastic leukemia or lymphoma without displaying a Cornelia-de-Lange syndrome phenotype [1], Michler et al identified a germline variant in POT1 in a child with acute myeloid leukemia and showed a connection between this variant and POT expression and telomeric dysregulation [2]. Regarding adult malignancies, Pacholewska et al identified local decreases in methylation levels in chronic lymphocytic leukemia patients harboring mutations at SF3B1, mostly in proximity to telomeric regions, enriched in cancer-related signaling genes [3], and Campos Gudiño et al observed that SKP1, CUL1, and F-box protein complex member genes were frequently altered at the genetic and epigenetic levels in many cancer types, which might contribute to the development and progression of these malignancies [4].…”
mentioning
confidence: 99%
“…While Schedel et al identified a germline variant in RAD21 that can predispose to childhood lymphoblastic leukemia or lymphoma without displaying a Cornelia-de-Lange syndrome phenotype [1], Michler et al identified a germline variant in POT1 in a child with acute myeloid leukemia and showed a connection between this variant and POT expression and telomeric dysregulation [2]. Regarding adult malignancies, Pacholewska et al identified local decreases in methylation levels in chronic lymphocytic leukemia patients harboring mutations at SF3B1, mostly in proximity to telomeric regions, enriched in cancer-related signaling genes [3], and Campos Gudiño et al observed that SKP1, CUL1, and F-box protein complex member genes were frequently altered at the genetic and epigenetic levels in many cancer types, which might contribute to the development and progression of these malignancies [4].…”
mentioning
confidence: 99%